GAMES FOR URBAN DESIGN-COMPARATIVE STUDY (International Journal of Food and Nutritional Sciences, 2022)
The primary emphasis of our article is on the integration of professional video games and internetgaming within the field of urban planning. From the beginning, we establish clear definitions for gamesand serious entertainment and discuss the potential of these specific forms of games. We offer anoverview of online urban planning games, along with gaming examples that encompass various topicsand storylines. In order to guarantee the precision of environmental measurements, a standardisedoperating process is established, uncertainty is evaluated, and quality assurance methods areimplemented. The main aim of the paper is to explore the potential of serious games in facilitatingpublic engagement in the planning process. We provide a concise summary of the selected games thatare now available for purchase. We opt to classify the accessible games according to their variety,distinguishing between traditional, digital, and non-digital gaming. The assortment ofanalog/conventional games comprises the subsequent titles: Masterplan, Neue Heimat, Pop-up Pest,Stadtspieler, Broken Cities, CLUG, and Ginkgo Polis; a few of these products have gained considerablerecognition, while others are more recent innovations. The computer games that we considered are:Plasticity, Securing Sydney's Planning and Development, SimCity, Anno, City One, Civilization,Community Plant, Green Sight City, and Minecraft/Block by Block. Some of the widely availablegames included Pac Manhattan, REXplorer, and Mogi. We evaluated them based on predeterminedcriteria, which encompassed knowledge transfer, learning effect, realistic visualisation, involvement,and engagement. One benefit was the realisation that certain games are used to incorporate students orparticipants into the urban planning process. An noteworthy observation is that although many gamesdealt with urban planning subjects, only a small number of them actively included players in real urbanplanning activities. As we conclude our research, we provide a thorough evaluation of the study's resultsand suggest areas for future investigation about the relationship between video games and urbanplanning.